Pengaruh Karakteristik Individu dan Lingkungan Kerja terhadap Loyalitas Melalui Motivasi sebagai Variabel Mediasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus - Darwanto, Darwanto (Jurnal Studi Manajemen Bisnis, 2022)
ABSTRACT This study aims to analyze the influence of individuals, and the work environment on work loyalty through motivation as a mediating variable at the Department of Public Works and Spatial Planning, Kudus Regency. The object of research at the Department of Public Works and Spatial Planning of Kudus Regency was used as research, so that data collection used questionnaires, so that it was a source of data in the form of primary data which was the result of distributing questionnaires and secondary data about the description of the object of research, the research sample was 111 respondents. Data processing using the computer program SEM AMOS Version 23. The results of the data analysis carried out can be concluded (1) There is a positive and significant effect of individual characteristics on the motivation of the Public Works and Spatial Planning Office of Kudus Regency. (2) There is a positive and significant effect of the work environment on the motivation of the Public Works and Spatial Planning Office of Kudus Regency (3) There is a positive and significant effect of individual characteristics on work loyalty at the Kudus Regency Public Works and Spatial Planning Office (4) There is a positive and significant influence work environment on work loyalty at the Office of Public Works and Spatial Planning in Kudus Regency (5) There is a positive and significant effect of work motivation on work loyalty at the Department of Public Works and Spatial Planning in Kudus Regency. ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh karakteristik individu, dan lingkungan kerja terhadap loyalitas melalui motivasi sebagai variabel mediasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus. Objek penelitian pada Kantor Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus dijadikan sebagai tempat penelitian, sehingga pengumpulan data menggunakan kuisioner,dan  sumber data berupa data primer yang merupakan hasil penyebaran angket dan data sekunder tentang gambaran mengenai objek penelitian, sampel penelitian sebanyak 111 responden. Pengolahan data menggunakan komputer program SEM AMOS Versi 23. Hasil analisis data yang dilakukan dapat ditarik kesimpulan (1) Ada pengaruh positif dan signifikan karakteristik individu terhadap motivasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus. (2) Ada pengaruh positif dan signifikan lingkungan kerja terhadap motivasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus (3) Ada pengaruh positif dan signifikan karakteristik individu  terhadap loyalitas  pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus (4) Ada pengaruh positif dan signifikan lingkungan kerja  terhadap loyalitas  pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus (5) Ada pengaruh positif dan signifikan motivasi  terhadap loyalitas  pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kudus.